The Influence of the Problem Based Learning (PBL) Model on Metacognitive and Learning Outcomes of Class VIII Students of SMP Negeri 37 Samarinda on Human Excretory System Material - Jusma; Nasution, Ruqoyyah; Akhmad; Masitah (Biosel Biology Science and Education, 2026)
Facing future challenges requires various skills to achieve success, one of which is metacognitive skills. Therefore, the use of science-based learning in the learning process not only aims to improve student learning outcomes, but also to empower their metacognitive skills. This research aims to determine the effect of using Problem Based Learning (PBL) on the metacognitive and learning outcomes of class VIII students at SMP Negeri 37 Samarinda.  This type of experimental research uses quantitative methods in the form of a quasi experimental design type, the pretest posttest control group design. The population in this study were all class VIII students at SMP Negeri 37 Samarinda. Sampling used a purposive sampling technique using classes according to the researcher's needs with a sample size of 48 students. The instrument analysis technique uses construct validity and reliability tests, while the analysis of research results uses the N-gain test, normality test, homogeneity test, and Wilcoxon test with a significance level of 5%. The results of data analysis show that the average value of students' metacognitive indicators after being treated in the experimental class was 80.67 in the very good category, while the control class was 79.58 in the good category. The average posttest score for experimental class learning outcomes was 69.82, while the control class was 38.02. The N-gain metacognitive questionnaire test in the experimental class was 0.27 in the low category, while the control class was 0.08 in the low category. The experimental class had an N-gain value for the cognitive learning outcomes test of 0.46 in the medium category, while the control class was -0.01 in the low category. The Wilcoxon test results on the metacognitive questionnaire and learning outcomes show the Asymp value. Sig. (2 tailed) of 0.000, this value is smaller than 0.05 so it can be concluded that there is an influence of the use of Problem Based Learning (PBL) on metacognitive and cognitive learning outcomes of class VIII students at SMP Negeri 37 Samarinda on the human excretion system material.  Keywords: Problem Based Learning, Metacognitive, Learning Outcomes